JURIDICAL ANALYSIS OF UNLAWFUL ACTS OF FORGERY OF FIDUCIARY GUARANTEES ARTICLE 35 AS REGULATED IN LAW NUMBER 42 OF 1999 CONCERNING FIDUCIARY GUARANTEES - Moh. Sigit Gunawan; Akmal Syaefulloh; Faisal Hambali; Octavia Sastra Agung; Agus Setiawan; Sylvia Rubyeta (Ann Publisher, 2025)
Abstract: Background: Fiduciary law was created to provide legal certainty and ease of access to credit in this regard, so the researcher is interested in juridically examining decisions related to the criminal acts of unlawful acts regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees. Aim: The primary focus of the research is to evaluate the judge's legal considerations in applying criminal provisions to the defendant, paying attention to the elements of criminal acts contained in the law. Methods: The research method used is normative legal research with a case analysis approach. The data includes court decisions, laws and regulations, and related legal literature. Results: The study's results show that judges vary in their application of the law in fiduciary guarantee cases. Conclusions: This analysis also highlights the implications of the ruling on legal certainty in fiduciary guarantee practice. Implication: This research is expected to contribute to developing legal understanding of fiduciary guarantees and judicial practices in Indonesia.